الآليات البلاغية ودورها الحجاجي في ديوان أطلس المعجزات لصالح خرفي - شودار, سامية (قــــــراءات; No 09 (2016): مجلة قراءات, 2019)
يسعى هذا المقال إلى بيان كيفية استثمار الآليات البلاغية في حجية الخطاب الشعري، ودورها الفعال في إقناع المتلقي، والآليات البلاغية هي جملة من الأساليب، تمكن المرسل من تأدية المعنى الذي يقصده، تأدية واضحة فصيحة، مع مراعاة المجاز. من هذا المنطلق تهدف الدراسة إلى تقديم التقنيات البلاغية التي أسهمت في حجية الخطاب الشعري في أطلس المعجزات لصالح خرفي؛ والمتمثلة في: تقسيم الكل إلى أجزائه، والتشبيه، والاستعارة، والكناية، والبديع.   ABSTRACT : This article seeks to show how investment rhetorical mechanisms in Authentic poetic discourse, and its active rolein persuading the recever, and mechanisms rhetoric are a number of methods that enable the sender to perform the sense in which he meant, perform and clear, fluent, taking into account the metaphor. From this point of this study aims to provide rhetorical techniques that have contributed to the authoritative poetic discourse in favor of Atlas el Moajizatte of saleh kharfi represented in the division to speak of its parts, and metaphor, and metonymy.